Design of a Transdermal Sustained Release Formulation Based on Water-Soluble Ointment Incorporating Tulobuterol Nanoparticles - Noriaki Nagai; Fumihiko Ogata; Saori Deguchi; Aoi Fushiki; Saki Daimyo; Hiroko Otake; Naohito Kawasaki (MDPI AG, 2022)
We aimed to investigate which base was suitable for preparing transdermal formulations incorporating tulobuterol (TUL) nanoparticles (30-180 nm) in this study. Three bases (water-soluble, absorptive, and aqueous ionic cream) were selected to prepare the transdermal formulations, and TUL nanoparticles were prepared with a bead-milling treatment. In the drug release study, the TUL release from the water-soluble ointment was higher than that from the other two ointments. Moreover, the addition of l-menthol enhanced TUL nanoparticle release from the ointment, and the rat skin penetration of the TUL water-soluble ointment was also significantly higher than that of the other two ointments. In addition, the drug penetration of the TUL water-soluble ointment with l-menthol sustained zero-order release over 24 h, and the skin permeability of TUL increased with TUL content in the ointment. On the other hand, this penetration was significantly inhibited by treatment with a caveolae-mediated endocytosis inhibitor (nystatin). In conclusion, we found that the water-soluble base incorporating TUL nanoparticles and l-menthol was the best among those assessed in this study. Furthermore, the pathway using caveolae-mediated endocytosis was related to the skin penetration of TUL nanoparticles in the TUL water-soluble ointment with l-menthol. These findings are useful for the design of a transdermal sustained-release formulation based on TUL nanoparticles.